2018
DOI: 10.1002/ajmg.c.31659
|View full text |Cite
|
Sign up to set email alerts
|

PHACE syndrome: Infantile hemangiomas associated with multiple congenital anomalies: Clues to the cause

Abstract: Infantile hemangiomas (IH) are the most common vascular tumor of infancy with an estimated 80,000 annual diagnoses in the United States. The genetic mechanisms underlying IH and the related multi‐organ birth defect syndromes, PHACE (an acronym for Posterior fossa brain malformations, segmental facial Hemangiomas, Arterial anomalies, Cardiac defects, Eye anomalies, and sternal clefting or supraumbilical raphe) and LUMBAR (an acronym for Lower body hemangiomas, Urogenital anomalies, Myelopathy, Bone deformities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…However, it arguably could have been considered in the differential diagnosis, given the presence of a large forehead hemangioma, even if it did not fully occupy the frontonasal segment. e ocular findings included congenital cataracts, a minor diagnostic criterion for PHACE, as well as congenital hypertrophy of the retinal pigment epithelium (CHRPE), a posterior segment anomaly that could be counted as a major diagnostic criterion [10]. She also had a cardiac ventricular septal defect, another minor criterion for PHACE diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it arguably could have been considered in the differential diagnosis, given the presence of a large forehead hemangioma, even if it did not fully occupy the frontonasal segment. e ocular findings included congenital cataracts, a minor diagnostic criterion for PHACE, as well as congenital hypertrophy of the retinal pigment epithelium (CHRPE), a posterior segment anomaly that could be counted as a major diagnostic criterion [10]. She also had a cardiac ventricular septal defect, another minor criterion for PHACE diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Her parents also reported that she had long roots of her teeth with one missing tooth and first primary tooth loss at 6-7 years of age ( Figure 6). Due to this important clinical observation and her cardiac history, genetic testing for this condition was performed, revealing a pathogenic monoallelic variant, c.2514del(G), p.Lys839Serfs * 17 consistent To further analyze any molecular genetic studies of PHACE that might shed light on BCOR's candidacy for this diagnosis, we performed a gene set enrichment pathway analysis (GSEA) (GSEA-Broad Institute [8,9], http:// software.broadinstitute.org/gsea/index.jsp) by adding BCOR to Sigel's (2018) gene list [10]. When BCOR is added among BRAF, GNA11, GNAQ, KRAS, MAP2K1, MTOR, NRAS, PIK3CA, PIK3R1, and RASA1, GSEA shows that BCOR overlaps significantly with other genes in the pathway of domain of "circulatory system development ( Figure 7).…”
mentioning
confidence: 99%
“…In addition, the genetics of PHACE syndrome has not been well-elucidated but is hypothesized to be secondary to low-level postzygotic variants. 20 Despite a candidate potential locus identified on 7q33 in 2 individuals, 21 more recent research suggests that the affected gene in PHACE syndrome has not been discovered because the variant allele frequency of the mosaic mutations is extremely low. 20 Further analysis with next-generation sequencing may provide causative mutations in PHACE syndrome.…”
Section: Conventional Mr Imaging Findingsmentioning
confidence: 99%
“…Siegel reviews PHACE syndrome (MIM 606519) and the highly‐related phenotype, LUMBAR syndrome, that combine infantile hemangiomas with multiple recurrent congenital anomalies (Siegel, ). While the etiology for these entities is not yet known, Siegel makes the argument that tissue‐specific low level mosaicism for known cancer genes is a compelling hypothesis that requires further study.…”
Section: Themes Of the Issuementioning
confidence: 99%